Bruch's membrane abnormalities in PRDM5-related brittle cornea syndrome. Issue 1 (December 2015) - Porter, Louise; Gallego-Pinazo, Roberto; Keeling, Catherine; Kamieniorz, Martyna; Zoppi, Nicoletta; Colombi, Marina; Giunta, Cecilia; Bonshek, Richard; Manson, Forbes; Black, Graeme
Abstract Background Brittle cornea syndrome (BCS) is a rare, generalized connective tissue disorder associated with extreme corneal thinning and a high risk of corneal rupture. Recessive mutations in transcription factorsZNF469 andPRDM5 cause BCS. Both transcription factors are suggested to act on a common pathway regulating extracellular matrix genes, particularly fibrillar collagens. We identified bilateral myopic choroidal neovascularization as the presenting feature of BCS in a 26-year-old-woman carrying a novelPRDM5 mutation (p.Glu134*). We performed immunohistochemistry of anterior and posterior segment ocular tissues, as expression of PRDM5 in the eye has not been described, or the effects of PRDM5-associated disease on the retina, particularly the extracellular matrix composition of Bruch's membrane. Methods Immunohistochemistry using antibodies against PRDM5, collagens type I, III, and IV was performed on the eyes of two unaffected controls and two patients (both with Δ9-14PRDM5 ). Expression of collagens, integrins, tenascin and fibronectin in skin fibroblasts of a BCS patient with a novel p.Glu134*PRDM5 mutation was assessed using immunofluorescence. Results PRDM5 is expressed in the corneal epithelium and retina. We observe reduced expression of major components of Bruch's membrane in the eyes of two BCS patients with aPRDM5 Δ9-14 mutation. Immunofluorescence performed on skin fibroblasts from a patient with p.Glu134* confirms the generalized nature of extracellular matrix abnormalities in BCS. Conclusions PDRM5-related disease is known to affect the cornea, skin and joints. Here we demonstrate, to the best of our knowledge for the first time, that PRDM5 localizes not only in the human cornea, but is also widely expressed in the retina. Our findings suggest that ECM abnormalities inPRDM5 -associated disease are more widespread than previously reported.